2022
DOI: 10.1002/vjch.202200054
|View full text |Cite
|
Sign up to set email alerts
|

Diketopiperazines from Rhabdastrella globostellata

Do Thi Trang,
Duong Thi Dung,
Dan Thi Thuy Hang
et al.

Abstract: From the methanol extract of the Vietnamese marine sponge Rhabdastrella globostellata (Carter, 1883), four diketopiperazines (1‐4) and one indol alkaloid (5) were isolated by various chromatographic methods. Their chemical structures were identified to be cyclo‐(L‐Pro‐L‐Ile) (1), cyclo‐(L‐Pro‐L‐Leu) (2), cyclo‐(D‐Pro‐L‐Ile) (3), cyclo‐(L‐Pro‐L‐Phe) (4), and tryptophol (5) by using a combination of ESI‐MS, 1D and 2D NMR spectral data as well as by comparison with previous literature. This is the first report of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…globostellata (Bourguet-Kondracki et al, 2000;Tasdemir et al, 2002;Clement et al, 2006;Fouad et al, 2006;Hirashima et al, 2010;Li et al, 2010;Trang et al, 2022a), and Spheciospongia spp. (Costantino et al, 2005;Whitson et al, 2008;Eltamany et al, 2015;Tawfike et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…globostellata (Bourguet-Kondracki et al, 2000;Tasdemir et al, 2002;Clement et al, 2006;Fouad et al, 2006;Hirashima et al, 2010;Li et al, 2010;Trang et al, 2022a), and Spheciospongia spp. (Costantino et al, 2005;Whitson et al, 2008;Eltamany et al, 2015;Tawfike et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously investigated the bacterial and archaeal diversity of the 18 marine sponge species and found that particularly three species Spheciospongia sp., Rhabdastrella globostellata and Clathria reinwardti harbored diverse communities of bacteria . Furthermore, recent chemical investigations have revealed diverse secondary metabolites derived from these sponge species, including C. reinwardti (Goud et al, 2005;Tai et al, 2021;Trang et al, 2022b), R. globostellata (Bourguet-Kondracki et al, 2000;Tasdemir et al, 2002;Clement et al, 2006;Fouad et al, 2006;Hirashima et al, 2010;Trang et al, 2022a), and Spheciospongia spp. (Costantino et al, 2005;Whitson et al, 2008;Eltamany et al, 2015;Tawfike et al, 2019).…”
Section: Introductionmentioning
confidence: 99%